1999
DOI: 10.1039/a807641c
|View full text |Cite
|
Sign up to set email alerts
|

Copper(I) Chloride/Kieselguhr: a Versatile Catalyst for Oxidation of Alkyl Halides and Alkyl Tosylates to the Carbonyl Compounds

Abstract: Copper(I) Chloride adsorbed on Kieselguhr in the presence of oxygen catalyses oxidation of alkyl halides and alkyl tosylates to the aldehydes and ketones in high yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…The oxidation of benzylic chlorides to the corresponding aldehydes has been reported using different systems, namely CuCl/Kieselguhr/O 2 [ 47 ], 2-dimethylamino- N , N -dimethylaniline N -oxide [ 48 ], 3,6-bis(triphenylphosphonium)cyclohexene peroxodisulfate [ 49 ], NaIO 4 -DMF [ 50 ], H 5 IO 6 in [C 12 mim][FeCl 4 ] ionic liquid [ 51 ], TEMPO (cat)/KNO 2 (cat)/O 2 [ 52 ], NMO/KI (cat) in [emim]Cl ionic liquid, MW [ 53 ] and molybdate-based catalyst/H 2 O 2 [ 54 ]. Based on that, we started this study by screening several oxidants (1.5 equiv.)…”
Section: Resultsmentioning
confidence: 99%
“…The oxidation of benzylic chlorides to the corresponding aldehydes has been reported using different systems, namely CuCl/Kieselguhr/O 2 [ 47 ], 2-dimethylamino- N , N -dimethylaniline N -oxide [ 48 ], 3,6-bis(triphenylphosphonium)cyclohexene peroxodisulfate [ 49 ], NaIO 4 -DMF [ 50 ], H 5 IO 6 in [C 12 mim][FeCl 4 ] ionic liquid [ 51 ], TEMPO (cat)/KNO 2 (cat)/O 2 [ 52 ], NMO/KI (cat) in [emim]Cl ionic liquid, MW [ 53 ] and molybdate-based catalyst/H 2 O 2 [ 54 ]. Based on that, we started this study by screening several oxidants (1.5 equiv.)…”
Section: Resultsmentioning
confidence: 99%
“…30 Moreover, kieselguhr is of special interest owing to its effectiveness in the retention of enzyme activity, 31 and its nice catalytic ability. 32,33 In this work, we incorporated HRP in the kieselguhr membrane. It was observed that HRP exhibits good direct electrochemical transfer reactions.…”
mentioning
confidence: 99%
“…In course of our systematic study of the development of supported reagents and catalysts for the oxidation of organic compounds, [16][17][18][19][20][21][22][23][24] we have nearly presented preparation and use of 4-aminoperoxybenzoic acid supported on silica gel as a convenient procedure for the oxidation of benzylic methylene compounds to corresponding ketones, [21] and for selective oxidation of aryl ketones to a-diketones. [23] Now we report that 4-aminoperoxybenzoic acid supported on silica gel is an efficient and convenient oxidant for the oxidation of ketones to esters in high yields (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%